Asignación presupuestaria y su relación con el gasto de personal en la unidad ejecutora de educación Ucayali Contamana Loreto periodo 2019-2023 - Landa Noriega, Hamlet Christean (2025)
Human talent management is a key element in public administration; however, poor human resources planning can lead to work overload and especially wage inequality, which negatively impacts productivity. Therefore, the present investigation aims to identify how the relationship between the budget allocation and the personnel expenditure is presented in the Ucayali Contamana Loreto education executing unit for the period 2019 - 2023, with an observational type of research, with a quantitative and non-experimental correlational approach, with a population made up of the budget records of the Ucayali Contamana Education Executing Unit, in which it was identified that there is a significant and positive relationship between the budget allocation and the personnel expenditure in the Ucayali Contamana Loreto education executing unit for the period 2019 - 2023. The work concludes that in the period 2019-2023, the budget allocation and the personnel expenditure in the Ucayali Contamana Loreto education executing unit presented a significant and positive relationship, with constant increases in both items. The budget allocation showed sustained and growing characteristics, reaching a cumulative total of 23,061,688 soles, while the execution of personnel expenses amounted to 436,300,140 soles, reflecting an effective approach in the management of resources for labor and social commitments. In addition, a positive trend was evident in the execution of remunerations and contributions, highlighting a significant growth in 2023, and a priority allocation towards remunerations and cash supplements, although with minimal execution in other remunerations.